Robotic-Assisted Total Knee Arthroplasty: Innovations, Outcomes, and Challenges – A Comprehensive Review - Umile Giuseppe Longo,; Di Benedetto, Matteo; Lavorato, Matteo; de Sire, Alessandro; D’Hooghe, Peter (Journal of Orthopaedics, Rehabilitation and Sports Medicine)
Background: Total knee arthroplasty (TKA) reliably relieves pain in end-stage knee osteoarthritis. Still up to 20% of patients report persistent dissatisfaction due to factors like component malalignment or soft-tissue imbalance. Robotic-assisted TKA has emerged to enhance surgical precision and enable patient-specific alignment strategies beyond the traditionally targeted neutral mechanical alignment. Purpose: To synthesize current knowledge on the role of robotic systems in TKA, including technological classifications, clinical outcomes, safety profile, economic considerations, and adoption challenges. Methods: A narrative literature review was conducted based on recent peer-reviewed publications, primarily focusing on robotic-assisted total knee arthroplasty (TKA). Articles were selected to reflect clinical outcomes, technological advances, surgical workflow evolution, and perioperative considerations related to robotic systems. While the review emphasizes robotic platforms, additional sources addressing conventional TKA were included to provide relevant clinical context. Included literature comprised systematic reviews, meta-analyses, registry reports, and cohort studies. Results: Semi-active robotic TKA systems consistently improve bone-cutting accuracy and alignment precision, dramatically reducing alignment outliers beyond 3° of neutral compared to conventional techniques. Robotic TKA has been associated with reduced early postoperative pain, faster recovery, and shorter hospital stays. Mid-term outcomes appear equivalent or slightly improved relative to conventional TKA, with similar safety profiles. Conclusion: Robotic-assisted TKA enhances surgical precision and early recovery without increasing complication risk. Long-term benefits, overall cost-effectiveness, and broad applicability of this technology remain under investigation.